2019
DOI: 10.3390/metabo9100239
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Understanding of the Bacterial Populations and Metabolites Profile of Fermented Feed by 16S rRNA Gene Sequencing and Liquid Chromatography–Mass Spectrometry

Abstract: The comprehensive bacterial populations and metabolites profile in fermented feed is unclear, which may have significant effects on the stability of fermented feed quality and animal gut health. In this study, 16S rRNA gene sequencing and liquid chromatography–mass spectrometry were used to explore the bacterial populations and metabolites profile in the fermented feed incubated with probiotics (MF) or without probiotics (SF). The probiotics were a combination of Lactobacillus salivarius, Bacillus subtilis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…However, previous studies have not reported the changes of microbial community and metabolite reaction during soybean fermentation, which were easy to be ignored. Firmicutes, Proteobacteria and Bacteroidetes were the main dominant phyla in different fermentations (Jin et al, 2019;Zhang et al, 2020a), which was consistent with our results. Our results also showed that Enterobacter and Bacillus were significantly enriched in enzymatic fermented soybean (Supplementary Figure 2).…”
Section: Discussionsupporting
confidence: 93%
“…However, previous studies have not reported the changes of microbial community and metabolite reaction during soybean fermentation, which were easy to be ignored. Firmicutes, Proteobacteria and Bacteroidetes were the main dominant phyla in different fermentations (Jin et al, 2019;Zhang et al, 2020a), which was consistent with our results. Our results also showed that Enterobacter and Bacillus were significantly enriched in enzymatic fermented soybean (Supplementary Figure 2).…”
Section: Discussionsupporting
confidence: 93%
“…The source of dipeptides and free amino acids is mainly caused by protease secreted by microorganisms that decompose the protein components of a Thai fermented soybean ( 43 ). Jin et al ( 44 ) found that L-theanine, glutamine, and glutamic acid enriched in the fermented corn, defatted soybean, and bran incubated with a combination of probiotics. Studies showed that the concentrations of most amino compounds gradually increased during fermentation with soybean as substrate ( 32 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that fermentation may enhance the bioavailability of feed nutrients by the following processes: (1) increasing crude protein content [ 4 ], (2) decreasing fiber content, (3) enhancing the utilization of vitamins, (4) improving amino acid patterns and protein solubility [ 5 ] and (5) degrading anti-nutritional factors with enzymes, such as phytase, xylanase, cellulase, and glucanase enzymes [ 6 ]. Besides this, the probiotics and metabolites produced during the fermentation process could reduce the colonization of gut pathogenic microorganisms via competitive exclusion and the secretion of antibacterial substances (like bacteriocin), and thus exert beneficial effects on animals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%